Illustration of HIV-1 protease folding through a molten-globule-like intermediate using an experimental model that implicates alpha-crystallin and calcium ions - Dash, C; Sastry, M; Rao, M (Biochemistry, 2005)
The folding of HIV-1 protease to its active form involves the coordination of structure formation and dimerization, which follows a hierarchy consisting of folding nuclei spanning from the active site, hinge region, and dimerization domain. However, the biochemical characteristics of the folding intermediates of this protein remain to be elucidated. In an experimental model, the denaturation of the tethered dimer of HIV-1 protease by guanidine hydrochloride revealed an alternative conformation resembling the molten globule state. The molten-globule state binds to the molecular chaperone alpha-crystallin and prevents its aggregation; however, the chaperone alone failed to reconstitute HIV-1 protease into its active form. Calcium ion assisted in the release of active enzyme from the chaperone complex. alpha-crystallin, a member of the small heat-shock protein, assists proteins to fold correctly; however, the underlying principle of signals responsible for chaperone-mediated protein folding remains enigmatic. X-ray photoelectron spectroscopy has been employed to provide the evidence of calcium binding to alpha-crystallin and to decipher the effect of calcium binding on the chaperone-mediated refolding of HIV-1 protease. On the basis of our spectroscopic data, we propose that calcium ions interact with the carboxyl groups of the surface-exposed acidic amino acids of alpha-crystallin bringing electrostatic interference, which plays a pivotal role in inducing conformational changes in the chaperone responsible for the release of the active enzyme.